Case report“Functional” surgery in epithelioid sarcoma of the hand – case report - Sobjanek, Michał; Michajłowski, Igor; Baczkowski, Bogusław; Wojszwiłło-Geppert, Elżbieta; Biernat, Wojciech; Włodarkiewicz, Adam (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Epithelioid sarcoma is a rare malignant soft tissue tumour that affects mainly young adults and shows a high risk of local recurrence. We present a 21-year-old male with epithelioid sarcoma developing in the hand which was histologically misdiagnosed as squamous cell carcinoma. The patient was treated with a wide excision without amputation and in a 5-year follow-up period was free of local recurrence and metastasis. The functional and aesthetic results were satisfactory. Our observation suggests that wide resection with free resection margins is an alternative to more aggressive treatment.